The Impact of Corporate Governance and Audit Quality on Earnings Management: Evidence from the Chinese Information Technology Industry. - Zheng, Yixin (2020)
This study integrates the characteristics of corporate governance and audit quality, and explores the impact of the two on earnings management. Since there are few existing literature concerning the rapid development of China's information technology industry in recent years, this study chooses Chinese information industry as the research background. In addition, this study selects listed companies in the information technology industry from 2017 to 2019 as samples. According to the modified Jones model, the absolute value of discretionary accruals is selected as the dependent variable to describe the degree of company earnings management. The research results show that there is a significant negative correlation between board size, director compensation, Big4 and 8 auditors and earnings management. On the other hand, gender diversity and audit fees have a significant and positive relationship with earnings management. In view of the board meeting, and the audit committee do not show its relevance to earnings management.